Patient and health-care provider experience of a person-centred, multidisciplinary, psychosocial support and harm reduction programme for patients with harmful use of alcohol and drug-resistant tuberculosis in Minsk, Belarus - Rebecca Elizabeth Harrison; Volha Shyleika; Christian Falkenstein; Ekaterine Garsevanidze; Olga Vishnevskaya; Knut Lonnroth; Öznur Sayakci; Animesh Sinha; Norman Sitali; Alena Skrahina; Beverley Stringer; Cecilio Tan; et al. (BMC, 2022)
Abstract Background Tuberculosis (TB) often concentrates in groups of people with complex health and social issues, including alcohol use disorders (AUD). Risk of TB, and poor TB treatment outcomes, are substantially elevated in people who have AUD. Médecins sans Frontières and the Belarus Ministry of Health have worked to improve treatment adherence in patients with multi-drug or rifampicin resistant (MDR/RR)-TB and harmful use of alcohol. In 2016, a person-centred, multidisciplinary, psychosocial support and harm reduction programme delivered by TB doctors, counsellors, psychiatrists, health-educators, and social workers was initiated. In 2020, we described patient and provider experiences within the programme as part of a wider evaluation. Methods We recruited 12 patients and 20 health-care workers, using purposive sampling, for in-depth individual interviews and focus group discussions. We used a participant-led, flexible, exploratory approach, enabling participants and the interviewer to shape topics of conversation. Qualitative data were coded manually and analysed thematically. As part of the analysis process, identified themes were shared with health-care worker participants to enable their reflections to be incorporated into the findings. Results Key themes related to the patients' and practitioners experience of having and treating MDRTB with associated complex health and social issues were: fragility and despair and guidance, trust and health. Prejudice and marginalisation were global to both themes. Counsellors and other health workers built a trusting relationship with patients, enabling guidance through a multi-disciplinary approach, which supported patients to achieve their vision of health. This guidance was achieved by a team of social workers, counsellors, doctors and health-educators who provided professional and individualised help for patients' illnesses, personal or interpersonal problems, administrative tasks, and job searches. Conclusions Patients with MDR/RR-TB and harmful use of alcohol faced complex issues during treatment. Our findings describe how person-centred, multi-disciplinary, psychosocial support helped patients in this setting to cope with these challenges and complete the treatment programme. We recommend that these findings are used to: i) inform programmatic changes to further boost the person-centred care nature of this program; and ii) advocate for this type of person-centred care approach to be rolled out across Belarus, and in contexts that face similar challenges.